The role of energy drink consumption in the intention to initiate marijuana use among adolescents. (June 2019) - Leal, Wanda E.; Jackson, Dylan B.
Abstract: Aims: The current study aims to examine whether energy drink consumption is associated with intentions to try marijuana among adolescents who have never tried marijuana, and whether the effects of energy drink consumption on the intention to try marijuana vary between adolescents who have previously tried alcohol or cigarettes and those who have not. Methods: This study employs a pooled cross-sectional design and uses a nationally representative sample of 8th (ages 13–14) and 10th (ages 15–16) grade adolescents from seven recent cohorts (2010–2016) of the Monitoring the Future (MTF) study. Logistic regression was employed to examine the association between energy drink consumption (none, light, moderate, heavy) and the odds of intending to initiate marijuana use in the next 12 months, controlling for sociodemographic factors and other health and social behaviors. Results: The results indicate that energy drink consumers are significantly more likely to intend to initiate marijuana use relative to non-consumers of energy drinks. Specifically, youth who heavily use energy drinks have significantly higher odds of having the intention to use marijuana in the near future than youth who consume energy drinks moderately or lightly. Additionally, evidence suggests that the relationship between energy drink consumption and the intention to use marijuana is moderated by use of other substances. Conclusions: The current study suggests that energy drink consumption (particularly heavy consumption) may be one early precursor in the escalation of substance use. It may be beneficial to include energy drinks in drug education curriculums. Highlights: Energy drink users are more likely to plan to use marijuana relative to non-users. Heavy energy drink users have the highest odds of intending to use marijuana. This relationship is stronger among youths with no alcohol or cigarette use.